EVALUASI MUTU GULA KELAPA KRISTAL (GULA SEMUT) DI KAWASAN HOME INDUSTRI GULA KELAPA KABUPATEN BANYUMAS - Pepita Haryanti; Mustaufik Mustaufik (Faculty of Agricultural Technology, University of Jember, 2011)
Coconut crystal sugar from Indonesia, especially from Banyumas Regency, have been often rejected by export markets due to the lack of variety and quality standards. Thus, it is important to review and evaluate the quality of coconut crystal sugar using statistical quality control methods. The purposes of this study were 1) to assess the quality deviations coconut crystal sugar in Banyumas Regency; 2) to investigate the diversity of coconut crystal sugar quality using both of histogram and control chart methods; 3) to determine factors that affect the quality of coconut crystal sugar using pareto diagram. This research was conducted by choosing purposively four sugar production center villages in Banyumas Regency, i.e. Dalawangi, Sokawera, Rancamaya, and Pageraji. The observed quality variables were water content, total sugar content, sugar content of sucrose, reducing sugar content, ash content, and insoluble materials. The data obtained were analyzed using histograms as well as control charts and pareto diagrams. Histogram analysis showed that ash content of the samples which is appropriate with Indonesian National Standard (SNI) was 27.5%. In addition, as many as 77.5% of the sugar moisture content was suitable with SNI, while for insoluble materials and reducing sugar content the suitable value were 70% and 97.5% of the total sample, respectively. Total sugar and sucrose content of all samples were appropriate with the SNI. The results of X and R control chart analysis were still largely under control. However, ash and water content as well as the insoluble material were out of control on the X control chart. Pareto diagram analysis results showed that the deviation of ash content, insoluble materials, and moisture content were 56.86%, 23.53%, and 17.65% of the total deviation, respectively. Keywords: coconut crystal sugar, histogram, control chart, pareto diagram